Evaluation of By-Products of Potato Peel as Food Additive - Yuksel, Ferhat; Durmaz, Aysun (Current Nutrition & Food Science, 2022)
Abstract: The potato plant is an important food source produced all over the world and it provides a significant portion of daily energy intake in nourishment. In addition, a significant rate of vitamins, fibre, mineral matters, protein, and fat can be obtained by consuming potato. In this study, the production, consumption, and usage areas of potato, a crucial source of our diet, and the possibilities of using it as food additives with the nutritional properties of its peel have been investigated. Generally, potato is consumed after its peel is removed in the homes and industrial areas and many of these peels are disposed off as wastes. Studies show that potato peel has a high content of dietary fibre, protein, carbohydrate, mineral matters, vitamin, phenolic, and antioxidant. The use of potato peel as food additives have also been discussed in this study.
Keywords: Potatoes